Secukinumab is effective in treatment of moderate‐to‐severe plaque psoriasis: real‐life effectiveness and safety from the PROSPECT study. (17th October 2019) - Thaçi, D.; Körber, A.; von Kiedrowski, R.; Bachhuber, T.; Melzer, N.; Kasparek, T.; Duetting, E.; Kraehn‐Senftleben, G.; Amon, U.; Augustin, M.
Abstract: Background: Secukinumab, a fully human anti‐interleukin‐17A monoclonal antibody, has demonstrated efficacy and safety in patients with moderate‐to‐severe psoriasis. Trial protocols specify transition periods and prohibit concomitant psoriasis medication. Data are therefore needed on secukinumab effectiveness and safety in routine clinical practice. Objectives: The PROSPECT study assesses prior and concomitant psoriasis treatments and transition periods in subjects receiving secukinumab. Here, we report interim effectiveness and safety data for secukinumab in the context of prior and concomitant treatments. Methods: PROSPECT is an ongoing 24‐week, single‐cohort, non‐interventional study. Subjects with moderate‐to‐severe psoriasis with a decision to receive secukinumab 300 mg were included. Results: Of 1988 subjects, 1238/1988 (62.4%) were male, and mean age was 48.1 ± 13.7 years. Mean baseline Psoriasis Area and Severity Index (PASI) score was 17.7 ± 12.5. 90.9% of subjects had prior systemic treatment. Concomitant treatment was recorded in 44.3% of subjects. Median duration of transition period was 14.0, 30.0 and 44.5 days from prior topical, conventional systemic and biologic treatments. At Week 24, PASI75/90/100 was reached by 86.1%, 68.5% and 39.7% of subjects who started secukinumab treatment at baseline. No unexpected safety signals were observed. Conclusion: PROSPECT provides a large prospective real‐world analysis of secukinumab treatment and includes prior and concomitant use of psoriasis treatments in subjects receiving secukinumab in a real‐world setting. Secukinumab effectiveness and safety were comparable to that seen in the phase 2/3 secukinumab clinical trial programme.